The Effect Of Digital Transformation On Company Performance In Umkm In The Food Industry With Innovation Business Model As A Mediation Variable - Muhamad Faizal Ardhian; Anjar Priyono (International Journal of Economics, Business and Innovation Research, 2025)
This research aims to 1) test and analyze the influence of digital transformation and company performance in MSMEs at the food souvenir center in Wonosobo, 2) test and analyze the company's performance in MSMEs in Wonosobo, 3) test and analyze the influence of digital transformation on company performance in MSMEs mediated by innovation business models. The type of research used in this research is convenience sampling. This research involved 133 MSMEs in Wonosobo Regency, Central Java. Using an analysis tool in the form of PLS-SEM, the results of this research show that 1) there is an influence of innovation business models on company performance, 2) there is an influence of digital transformation on innovation business models, 3) there is an influence of digital transformation on company performance. 4) there is an influence of the mediating role of innovation business models on company performance. And there is an influence of the mediating role of innovation business models on digital transformation.